The Accumulation of Key Stroke Risk Factors and Its Association With the Characteristics of Subjects: A Population Based Cross Sectional Study - Zhang, Peng; Jin, Hang; Guo, Zhen-Ni; Sun, Hui-Jie; Zhang, Fu-Liang; Sun, Xin; Yang, Yi (Frontiers in Neurology, 2018)
Background: Evidence has shown that the greater the accumulation of risk factors for stroke, the greater the risk of stroke. Early intervention in the accumulation of risk factors for stroke can effectively reduce the incidence of stroke. The study aimed to investigate the distribution of the number of certain risk factors for stroke (hypertension, hyperlipidemia, overweight and obesity, and diabetes) and to explore the cause of the accumulation of certain stroke risk factors. Methods: A total of 4052 participants aged 40 years or older were selected by the multistage stratified cluster sampling method in Dehui City in Jilin province, China. Descriptive data analyses were conducted. Multiple regression analyses were used to explore the adjusted association between the accumulation of key stroke risk factors and subjects' lifestyle and demographic characteristics. Results: Overall, 84.1% of the participants in this study had one or more of the four certain risk factors for stroke. The odds ratios (ORs) and 95% confidence intervals (CIs) of having ≥1, ≥2, and ≥3 key stroke risk factors were 1.627 (1.258, 2.103), 1.446 (1.209, 1.728), and 1.394 (1.164, 1.670), respectively, for males compared to females. Similarly, the ORs and 95% CIs of having ≥1, ≥2, and ≥3 key stroke risk factors were 1.227 (1.009, 1.492), 1.256 (1.096, 1.442), and 1.450 (1.262, 1.667), respectively, for partially salty diets compared to normal diets. Compared to people who did not exercise regularly, the ORs and 95% CIs of having ≥1, ≥2, and ≥3 key stroke risk factors were 0.693 (0.544, 0.883), 0.800 (0.679, 0.944), and 0.775 (0.659, 0.913), respectively, for people who regularly exercised. Compared to people who without a family history of cerebrovascular diseases, the ORs and 95% CIs were 1.418 (1.162, 1.732), 1.327 (1.154, 1.525), and 1.209 (1.050, 1.393), for people who with it. Conclusions: Male, partially salty diets, and family history of cerebrovascular diseases were risk factors for the accumulation of certain stroke risk factors while regular physical exercise was a protective factor.